The Potential Effect of the Black Seed (Niagella Sativa) Extract on Heamato-Biochemical Profile on Streptozotocin (STZ) – Induced Diabetic Mice - Sahib, Ahmad Hassan; Al-Yasiri, Zainab Qasim Muhammad; Al-Musawi, Ali Habeeb Odah (American Journal of Bioscience and Clinical Integrity, 2025)
Context: Diabetes is related with both hematological and biochemical complications. Combination medical treatment has been recommended as a strategy to decrease the influence of these-related complications. Aim: This study was designed to investigate the protective effects of Nigella sativa seed extract (NSSE) on some hemato-biochemical parameters in streptozotocin (STZ)- induced diabetic mice. Method: Streptozotocin (STZ)-induced diabetic mice received medication with Nigella sativa seed extract at doses of 125, 250 and 500 mg/kg or glibenclamide, once a day for 4 weeks. Specimens from blood were taken on day 28 for hematological and biochemistry analysis. The many hematological indices that were examined were , red blood cell count (RBCs), hemoglobin (HB) mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH),packed cell volume (PCV), mean corpuscular hemoglobin concentration (MCHC) and platelets count (PC), the total white blood cell count (WBC) was evaluated, in addition to a differential count of white blood cells, including lymphocytes, neutrophils, monocytes and eosinophils. On other hand, serum biochemical indices analyzed were serum glucose level (Glu), blood urea nitrogen (BUN), cholesterol (Chol), serum creatinine (Crt) ,bilirubin "bile pigment" (Bil), serum protein and enzymes level, alanine phosphate (ALP),alanine transaminase (ALT) ,aspartate transaminase (AST) total protein (TP) and albumin (ALB). Results: The results showed that Nigella sativa seed extract (NSSE) had positive benefits on hematological profile including, packed cell volume (PCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), and red blood cells (RBC), among others, while also dramatically lowering blood glucose and cholesterol levels. In addition, it reduced both kidney and liver damage, among other diabetes effects, and might have liver-protective activities. Conclusions: According to the results of this current study, Nigella sativa seed extract (NSSE) significantly effects on certain hemato-biochemical investigations, in comparison with metformin identified as guideline anti- hyperglycemic medication. Subsequently, the herbal extracts under current inquiry could have a role in alleviating the risk of certain chronic complications associated with diabetes.